Resuspended freeze-dried Nannochloropsis as a model laboratory system for concentrated fresh Nannochloropsis in ultrasound cell disruption experiments - Mienis, Esther; Vandamme, Dries; Foubert, Imogen (Frontiers in Marine Science, 2024)
Microalgae have rigid, complex cell walls hindering direct lipid extraction. Cell disruption techniques are used to rupture these cellular structures to increase lipid extraction. Researchers investigating the downstream processing of microalgae do not always have access to microalgal cultivation systems to generate large amounts of fresh microalgal biomass. Using resuspended freeze-dried microalgal biomass as a model laboratory system for concentrated fresh biomass during cell disruption experiments offers greater flexibility in experimental planning and omits investment costs of microalgal cultivation equipment. So far, it however remains unclear whether freeze-dried resuspended biomass can be used as a model laboratory system to represent concentrated fresh biomass during cell disruption and lipid extraction experiments. This paper thus evaluated the suitability of resuspended freeze-dried Nannochloropsis as a model laboratory system for concentrated fresh Nannochloropsis during cell disruption. Ultrasound assisted cell disruption was used as example cell disruption technique and lipid extraction efficiency and free fatty acid content were investigated. Tap water and 3% sodium chloride are both suitable resuspension media for the resuspension of freeze-dried Nannochloropsis. Resuspension duration should be limited (< 120 min) to prevent the formation of free fatty acids. The condition of the biomass (concentrated fresh, or resuspended freeze-dried) prior to ultrasound assisted cell disruption did not influence the resulting lipid extraction efficiency. Resuspended freeze-dried Nannochloropsis biomass in tap water or 3% sodium chloride can thus be used as a model laboratory system for fresh microalgal biomass during research on ultrasound assisted lipid extraction. The generalization of the results to other cultivation conditions, cell disruption techniques, components of interest or microalgal species should be carefully assessed.